Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Melalui Permainan Sepakbola Terhadap Kepercayaan Diri Dan Keterampilan Gerak Dasar Pada Siswa Sekolah Dasar - Khamdani, Muhammad Nauval (Jurnal MensSana, 2025)
This study aims to determine the effect of applying the Jigsaw cooperative learning model on self-confidence and basic football skills of fifth-grade students at SD Negeri 1 Suranenggala, Cirebon Regency. The research method used was a quasi-experimental design with a Pretest-Posttest Control Group Design. The sample consisted of 20 male students in the fifth grade, selected using a purposive sampling technique. The research instruments included the Game Performance Assessment Instrument (GPAI) to measure football playing skills and the Athlete Self-Confidence Questionnaire (ASQ) to assess students’ self-confidence. Data were analyzed using normality, homogeneity, and paired sample t-tests.The results showed a significant improvement in both self-confidence and basic football skills after the implementation of the Jigsaw model. The average pretest score of football skills was 2.38, which increased to 3.18 in the posttest. The paired t-test revealed a significance value of Sig. (2-tailed) = 0.000 < 0.05, indicating a significant difference between pretest and posttest results. In conclusion, the Jigsaw cooperative learning model has a positive and significant effect on enhancing students’ self-confidence and basic football skills in elementary school.